Assistance in the Development of Interactive Liveworksheet-Based Student Worksheets with the AKMI Model to Improve Students' Literacy Numeracy at MI Nurul Huda - Mohammad Nurwahid; Nezar Subiantoro; Nur Laella Romadhoni (STKIP Singkawang, 2026)
The low level of numeracy literacy among madrasah students, as indicated by AKMI results, is partly caused by teachers’ limited ability to develop digital-based learning materials. This community service program assisted teachers at MI Nurul Huda Sawo, Gresik, in developing interactive Liveworksheet-based worksheets aligned with the AKMI model through a participatory approach over three months. The results showed improved teacher competence and a 20–25% increase in students’ numeracy literacy, accompanied by higher learning motivation. The program produced interactive worksheets, enhanced teachers’ digital teaching capacity, and a nationally published scientific article.Pendampingan Pengembangan LKPD interaktif Berbasis Liveworksheet dengan Model AKMI untuk Meningkatkan Literasi Numerasi Siswa di MI Nurul HudaABSTRAKRendahnya literasi numerasi siswa madrasah berdasarkan hasil AKMI dipengaruhi keterbatasan guru dalam mengembangkan perangkat pembelajaran digital. Kegiatan pengabdian ini mendampingi guru MI Nurul Huda Sawo, Gresik, dalam mengembangkan LKPD interaktif berbasis Liveworksheet dengan model AKMI melalui pendekatan partisipatif selama tiga bulan. Hasilnya menunjukkan peningkatan kompetensi guru serta peningkatan literasi numerasi siswa sebesar 20–25%, disertai meningkatnya motivasi belajar. Luaran kegiatan berupa LKPD interaktif, peningkatan kapasitas guru, dan publikasi artikel ilmiahKata Kunci :Literasi Numerasi; LKPD Interaktif; Liveworksheet; AKMI; Pengabdian Kepada Masyarakat